Antibiogram Pattern of Bacterial Isolates from Sputum Sample - Nyaupane, Krishna; Mahat, Nikita; Lamichhane, Apsara; Bhainatwo, Binita; Parajuli, Pustika (International Journal of Applied Sciences and Biotechnology, 2024)
Antibiotics are frequently used for various infectious disease example; acute lower respiratory tract infection. But, injudicious use of antibiotic resistance is an emerging problem. The objective of this study was taken up to analyze the antibiogram pattern of bacterial isolated from the sputum samples of patient in Manmohan Memorial Medical College and Teaching Hospital. Initially, 250 sputum specimens of patients were collected and opted for the isolation and identification of isolates which detected 56.097% Klebsiella spp. 17.073 %, Pseudomonas aeruginosa 4.878 %, Burkholderia spp. 9.756 % Enterobacter spp. 12.195% Escherichia coli respectively. Conducting AST following Kirby Bauer disc diffusion method (CLSI 2020), it was determined that Klebsiella spp. (56.097 %) exhibited sensitive to Gentamycin and exhibited resistance to Cefixime. It was observed that 9 (39.130 %) Klebsiella spp. isolates exhibited multi-drug resistance character. Likewise, out of 23 isolated Klebsiella spp. only 5 (21.739 %) was found to be ESBL producers. The presence of multi drug-resistant strains and Extended Spectrum Beta-Lactamase (ESBL) producing Klebsiella spp. is of major concern worldwide. The improper and excessive utilization of antibiotics, encompassing unauthorized practices might be the reason in the rise to the development and proliferation of antimicrobial resistance (AMR) and multidrug resistance (MDR)in microorganisms. This study highlights the importance of implementing appropriate hygiene and dietary measures for human to prevent the transmission of diverse pathogenic microorganisms. Int. J. Appl. Sci. Biotechnol. Vol 12(3): 151-157.